KEUNGGULAN BUDAYA DALAM RANGKA INTEGRASI KAWASAN DAN KESEJAHTERAAN BERSAMA: ANALISIS TERHADAP TEKS TANTU PANGGELARAN DAN USANA BALI - I Nengah Duija (Faculty of Humanities, Jember University, 2014)
The development of science and technology, especially communication and transportation, stimulates a fast globalization. Strong nation integrity and identity or personality are necessary for intercultural meeting to run well, living in harmony, and mutual respect. The results of the study on ancient texts, written and oral- show that cultural heritage can provide added value to the lives of modern people today. Texts like Tantu Panggelaran and Usana Bali need to continue to get their meaning by each generation. The results of the analysis of the two texts show that the majesty of ancient civilizations is able to create a frame of togetherness, social and geographic frames, and cross-border regions and countries geopolitics. The frame as a mythology that directs how to get a togetherness creating the names of the mountains, areas, villages, rivers, and religious understandings. That is the meaning of togetherness and prosperity that will be achieved (jagathita) or happiness in the universe. Keywords: mythology, unity, prosperity, happiness